Studi Kelayakan Lokasi Budidaya Kerapu (Epinephelus sp.) di Perairan Pulau-Pulau Sembilan, Kabupaten Sinjai, Sulawesi Selatan - Utojo Utojo; Abdul Mansyur (Jurnal Perikanan Universitas Gadjah Mada, 2007)
This study was conducted to find out location which was suitable for culture of grouper (Epinephelus sp.) in Pulau-Pulau Sembilan waters, Sinjai Regency, South Sulawesi. The primary data were collected from each study areas as grouper culture requirement i.e: coastal topography, from the high wave and current, water quality and biological parameters. Secondary data such as wheather, coastal fisheries production, tide probability, Indonesia earth surface map of Sinjai area scale of 1: 75,000, landsat imagery-7ETM digital product and navigation map scale 1: 200,000 were collected before the study. Thematic map of area, suitability as the main expected output of the study was made through spatial analysis and Geographical Information System (GIS). The site suitability for grouper culture in floating net cage was evaluated based on the physical oceanography as limited factors, where factors which influences to the grouper growth and survival were given highest value.The range of values was 0-1. The level of suitability at the value of 1-4, where 4 (100%) = S1 (most suitable), 3 (75-99%) = S2 (suitable), 2(50-74%) = S3 (fair suitable) and 1 (< 50%) = N (less suitable). The potential areas which were suitable for grouper culture in floating net cage development was 303.4 hectares.